PENGARUH KUAT ARUS LISTRIK PADA PENGELASAN METAL INERT GAS (MIG) TERHADAP SAMBUNGAN LOGAM ALUMINIUM - Laumma, Muhammad Alwi; Yunus, Kartini (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2024)
The aim of this research is to calculate and compare the tensile strength of MIG welding with different current variations, apart from that it can also obtain optimal electric current variations in MIG (Metal Inert Gas) welding, electric current variations namely 150 amperes, 155 amperes and 160 amperes. Data from tensile test results using ASTM B 557M 02-a standard with the highest tensile stress value obtained in welding using a current of 155 amperes, namely 13.03 kg/mm² and the lowest tensile stress value at a current of 160 amperes 9.47 kg/ mm².